Predictive Value of COPD History on In-Stent Restenosis in Coronary Arteries Following Percutaneous Coronary Intervention - Hou L; Su K; Zhao J; Li Y (International Journal of General Medicine, 2023)
Ling Hou,1 Ke Su,2 Jinbo Zhao,2 Yuanhong Li2 1Department of Central Hospital of Tujia and Miao Autonomous Prefecture, Hubei University of Medicine, Shiyan, Hubei Province, People’s Republic of China; 2Cardiovascular Disease Center, Central Hospital of Tujia and Miao Autonomous Prefecture, Hubei University of Medicine, Enshi, Hubei Province, People’s Republic of ChinaCorrespondence: Yuanhong Li, Email lyh0101@vip.comObjective: Chronic obstructive pulmonary disease (COPD) is a prevalent chronic respiratory disease that poses a significant health risk to individuals. Patients with COPD are predisposed to a higher incidence of coronary artery disease (CAD) than the general population. This study aims to investigate the correlation between COPD and the incidence of in-stent restenosis (ISR) after percutaneous coronary intervention (PCI).Methods: This study retrospectively analyzed the clinical data and laboratory test results of patients who underwent PCI at our hospital between January 2018 and December 2021 to investigate the relationship between COPD and drug-Eluting Stents (DES) postoperative ISR. We employed the best subset method to select the most suitable combination of predictive factors, utilizing the data, and verified the precision of the model by means of internal validation. We ultimately assessed the performance of the prediction model using an ROC curve.Results: The research indicates that COPD is an independent risk factor for ISR after PCI (OR=2.437, 95% CI [1.336, 4.495], P=0.004). The analysis revealed an area under the receiver operating characteristic (ROC) curve of 0.783 for the training group and 0.705 for the testing group, indicating a model fitting for both groups (both > 0.5).Conclusion: COPD history is a dependable predictor of stent restenosis post percutaneous coronary intervention.Keywords: percutaneous coronary intervention, PCI, chronic obstructive pulmonary disease, COPD, in-stent restenosis, ISR, drug-eluting stents, DES, optimal subset regression